Heteroatom‐induced tensile strain in copper lattice boosts CO2 electroreduction toward multi‐carbon products - Zhiyang Zhai; Deliang Li; Xin Lu; Huizhu Cai; Qi Hu; Hengpan Yang; Chuanxin He (Carbon Energy)
Abstract Strain engineering on metal‐based catalysts has been utilized as an efficacious strategy to regulate the mechanism and pathways in various electrocatalytic reactions. However, controlling strain and establishing the strain‐activity relationship still remain significant challenges. Herein, three different and continuous tensile strains (CuPd‐1.90%, CuAu‐3.37%, and CuAg‐4.33%) are successfully induced by introducing heteroatoms with different atomic radius. The catalytic performances of CuPd‐1.90%, CuAu‐3.37%, and CuAg‐4.33% display a positive correlation against tensile strains in electrochemical CO2 reduction reaction (CO2RR). Specifically, CuAg‐4.33% exhibits superior catalytic performance with a 77.9% Faradaic efficiency of multi‐carbon products at −300 mA cm−2 current density, significantly higher than those of pristine Cu (Cu‐0%). Theoretical calculations and in situ spectroscopies verify that tensile strain can affect the d‐band center of Cu, thereby altering the binding energy of *CO intermediates and Gibbs free energies of the C–C coupling procedure. This work might highlight a new method for precisely regulating the lattice strain of metallic catalysts in different electrocatalytic reactions.